(3cTa GdCSQGQ Yf Yde MQha GdZHGQs - (3Ydj Hf eMeO Hf eMeO Hf Ydj GdbQTi GdTgjQ HGdbdUGhis; (3Ydj Hf eMeO Hf eMeO Hf Ydj GdbQTj, GdbdUGhj GdHSjWjs ((3CMeO GdOefghQi s)
(3ChdgG (B:s
(3GdMeO ddg SQjY GdMSGH eSHd GdfgGQ haGJM GdCHhGH hGdUdGI hGdSdGe Ydi SjO Gdchfjf CeG HYO agPg fHPI cGajI EbJWaJgG ef cJGHi GdeSei HcTa GdLdHGH Yf Yde GdMSGH hSejJgG cTa GdCSQGQ s
(3BNQgG (B:s
(3hgPG BNQ eG bUOfG ef gPG GdehVhY Efg hdi GdJhajb hUdi Gddg Ydi SjOfG eMeO hYdiBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs